Donnybrook [videorecording (DVD)] - Sutton, Tim (Director); Sutton, Tim (Director); Grillo, Frank, 1963-; Qualley, Margaret; Bell, Jamie, 1986-; Bill, Frank, 1974- (Shout! Factory, 2019)
Three desperate people discover that the way out of their current lives is to win a bare knuckle fighting match.